Yale football through the years - Marazzi, Richard (McFarland & Company, Inc., Publishers, 2020)
"Chronicling Yale football from its 1827 inception to the present, this volume gives comprehensive coverage of the most important games, including all Yale-Harvard contests, most Yale-Princeton, record-making performances, great plays and more. Human-interest anecdotes offer a sidebar to the game or era covered, giving color to the storied history of Yale football. The evolution of rules is traced, that transformed a game combining soccer and rugby into the football we know today."--